PREPARATION OF THE FUTURE MANAGERS OF ESTABLISHMENTS AND ORGANIZATIONS IN EDUCATIONAL SPHERE IN GREAT BRITAIN AND UKRAINE - Binyts’ka, O. (Continuing Professional Education: Theory and Practice, 2019)
The author reveals theoretical approaches on the problem of preparation of future managers of establishments and organizations in educational sphere in Great Britain and Ukraine, interprets the views of other researchers. The process of preparation of the future managers of establishments and organizations is analyzed in educational sphere at graduate courses of higher educational establishments.Researches and publications on the problems of preparation of the future managers of institutions and organizations in educational sphere in Great Britain and Ukraine are characterized. Analysis of statutory and regulatory documents of Great Britain and Ukraine as for the problem of publication is done. It is determined that both in Great Britain and in Ukraine the educational process of preparation of the future managers of institutions and organizations in educational sphere is carried out taking into account didactic abilities of the modern informationcommunicational technologies of education, and it is oriented to formation of well educated, harmoniously developed personality, able to selfeducation, constant renewal of scientific knowledge, professional mobility, quick adaptation to the changes in socialcultural sphere, systems of management and organization of work under the conditions of market economy.